Meals adequacy during weekdays and weekends in an Italian primary school children sample. (20th October 2021) - Soldà, G; Salussolia, A; Zanutto, G; Sanmarchi, F; Marini, S; Dallolio, L; Ferretti, F; Arrichiello, F; Lorenzini, A; Masini, A
Abstract: Background: Between 15 and 50% of European children aged 6-9 are overweight or obese and this number is rising dramatically over time, making it one of the most important public health challenges. Selection of healthy food and a balanced diet are key when addressing this obesity epidemic. At the same time, it is essential to consider schools' role and parents' influence on children's dietary habits. This study aims to assess the adequacy of meals during the weekdays (WD) and weekends (WE), therefore highlighting the critical moments where schools' and parents' involvement needs to be of greater impact. Methods: A cross-sectional study was conducted among 428 children aged 6-11 recruited in a primary school of Calderara di Reno (Italy) in 2017. A weekly diary was administered between May and June 2017 to explore the dietary habits of the participants. Every day for each meal (breakfast, morning snack, lunch, dinner) it was required to report what types of food and beverages were consumed, and where (home/school). The adequacy of each meal was determined by using national guidelines. A McNemar test was performed to evaluate the differences in meal adequacy between the WD and WE. Results: Our analysis showed that meals consumed at school, i.e. morning snacks and lunches, were more adequate during WD than WE (69.6% vs 22.2%, 53.5% vs 32.5%; P-value <0.001), underlying the positive influence of school. On the other hand, breakfasts and dinners were more adequate during WE than WD (64.5% vs 51.4%, 23.8% vs 15.7%; P-value <0.001); this difference might be partially explained by the different amount of time parents have for food preparation during workdays versus weekends. Conclusions: Further preventive interventions should address childrens' and parents' home dietary routine as a tool to improve meal adequacy at home and therefore reduce childhood obesity. Parental school-based interventions could have a key role in changing childrens' dietary habits. Key messages: Our study showed a significant difference of healthy dietary habits between meals served at school during weekdays and at home during weekends, highlighting a higher dietary adequacy in the first ones. The results underline the importance of implementing educational programs addressing childrens' and their parents' home meals routine and dietary habits.